THE HERMENEUTICAL STRATEGY AND PRIBUMISASI OF HADITH IN THE JAVANESE SYARAH OF MISBAH AL-ANAM FI TARJAMAH BULUGH AL-MARAM BY A. SUBKI MASYHADI - Su'aidi, Hasan; Dimyathi, Aniq (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
This research analyzes the methodology of hadith commentary in the book Miṣbāḥ al-Anām fī Tarjamah Bulūgh al-Marām by A. Subki Masyhadi, a prolific scholar from Pekalongan. Utilizing a descriptive-qualitative method with content analysis techniques, this study reveals Masyhadi’s hermeneutical strategies in bridging authoritative classical texts with the socio-cultural realities of Javanese society. The findings indicate the use of a combined ijmālī (global) and muqārin (comparative) method, integrated through three primary approaches: textual, contextual, and intertextual. Masyhadi maintains the orthodoxy of the pesantren tradition by referencing the Qur'an, Shafi'i jurisprudential literature, and linguistic authorities such as al-Nihāyah and Subul al-Salām. The originality of Masyhadi’s work lies in its massive effort toward the